2019
DOI: 10.1590/1678-4162-9676
|View full text |Cite
|
Sign up to set email alerts
|

Silage of rehydrated corn grain

Abstract: The objective with this study was to evaluate the effect of different levels of water inclusion on the chemical composition and fermentation profiles of reconstituted corn grain silage. The experiment was carried out in a factorial arrangement in a completely randomized design, with three replicates per treatment. Five treatments were evaluated with different levels of water inclusion (% of the natural matter): dry corn grain (control); 90% dry corn grain (DCG) and 10% water; 80% DCG and 20% water; 70% DGC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 11 publications
2
8
1
1
Order By: Relevance
“…Also, the lower concentration of lactic acid and higher pH were probably in part due to the clostridial fermentation that converts lactic acid to butyric acid (McDonald et al, 1991). Mombach et al (2019) also reported the benefits of increasing moisture content of RCG, with an improved fermentation pattern (low pH associated with less loss of gas and effluent) observed at approximately 38% of moisture. In our study, the concentration of butyric acid was highest in RCG with 30% of moisture compared with other treatments.…”
Section: Discussionmentioning
confidence: 88%
“…Also, the lower concentration of lactic acid and higher pH were probably in part due to the clostridial fermentation that converts lactic acid to butyric acid (McDonald et al, 1991). Mombach et al (2019) also reported the benefits of increasing moisture content of RCG, with an improved fermentation pattern (low pH associated with less loss of gas and effluent) observed at approximately 38% of moisture. In our study, the concentration of butyric acid was highest in RCG with 30% of moisture compared with other treatments.…”
Section: Discussionmentioning
confidence: 88%
“…Corn (Zea mays L.) is one of the main ingredients used in ruminant diets to increase energy levels and animal performance (Bernardes & Rêgo, 2014;Mombach, Pereira, Pina, Bolson, & Pedreira, 2019;Daniel, Bernardes, Jobim, Schmidt, & Nussio, 2019). This is related to the chemical composition that contains 879.6 g kg -1 dry matter, 205.1 g kg -1 water-soluble carbohydrates and 714.5 g kg -1 starch (Valadares et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, farms do not have adequate structures for storing corn and other cereals for use in animal feed throughout the year. The consequence of this lack of structure for storing grains is the damage caused by rodents, insects and fungi (Mombach et al, 2019). rehydrated (reconstituted) Thus, corn grain silage has been used to circumvent these losses (C. M. Silva et al, 2016), and to improve the starch digestibility of corn (Ferraretto, Silva, Fernandes, Kim, & Sultana, 2018) and nutrient utilization by ruminants (Castro et al, 2019;Jacovaci, Salvo, Jobim, & Daniel, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…O grau de estabilização é obtido com maior rapidez nos silos experimentais que nos comerciais, já que as condições para que ocorra o processo de fermentação anaeróbica se dá em menor tempo alterando os resultados. No Brasil, foram realizados poucos experimentos (PEDROSO et al, 2014;BUENO et al, 2020;MARTIN et al, 2012;TAVARES et al, 2009;TAVARES et al, 2019;OLIVEIRA et al, 2011;BUSO et al, 2018;CRUZ et al, 2019;NEUMANN et al, 2007;OLIVEIRA et al, 2013;MOMBACH et al, 2019) buscando estudar os microssilos experimentais utilizados para avaliação da silagem que se aproxime das condições de campo.…”
Section: Introductionunclassified